Isbat Nikah Poligami Ditinjau dari Maslahah mursalah Al-Shatiby: Studi SEMA Nomor 3 Tahun 2018 - Muhammad Nasrulloh; M. Fauzan Zenrif; R. Cecep Lukman Yasin (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2021)
The presence of SEMA Number 3 of 2018, which prohibits polygamy marriage, hurts women. This is because women do not have legal power over their marriages and cannot access the legal umbrella through the only way, namely the isbat of marriage. The logical consequence of this is that when their husbands neglect siri polygamous women, women undoubtedly have difficulty demanding their rights and difficulties in giving up their status. This study seeks to dissect the interests of polygamous siri women by considering aspects of their benefit. The study's focus is to answer how the position of polygamous marriage when juxtaposed with women's interests is still prohibited or allowed. The study carried out was a normative study with the maslahah mursalah Al-Shatiby as the analysis tool. The final hypothesis illustrates that it is precisely the prohibition of marriage to have an impact on women. This is because the maslahah of prohibiting marriage is assumptive, while the negativity of a woman whom her husband ignores is factual. Therefore, the prohibition of SEMA number 3 of 2018 must be re-read and studied more deeply in the interests of polygamous women in siri.   Abstrak: Hadirnya SEMA Nomor 3 tahun 2018 yang melarang isbat nikah poligami berdampak mudlarat atas perempuan. Pasalnya perempuan tidak memiliki kekuatan hukum atas pernikahannya dan tidak bisa mengakses payung hukum melalui satu-satunya jalan yakni isbat nikah. Konsekuensi logis dari hal tersebut adalah ketika perempuan poligami siri diabaikan oleh suaminya, niscaya perempuan kesulitan menuntut haknya dan kesulitan pula melepaskan statusnya. Kajian ini berusaha membedah kepentingan perempuan poligami siri dengan mempertimbangkan aspek kemaslahatannya. Fokus kajian guna menjawab bagaimana kedudukan isbat nikah poligami jika disandingkan kepada kepentingan perempuan apakah tetap dilaranga atau diperbolehkan. Telaah yang dilakukan bersifat kajian normatif dengan maslahah mursalah Al-Shatiby sebagai pisau analisisnya. Hipotesa akhir menggambarkan bahwa justru pelarangan isbat nikah berdampak mudlarat kepada perempuan. Sebab maslahah pelarangan isbat nikah bersifat asumtif sedang kemudlaratan perempuan yang diabaikan suaminya bersifat faktual. Oleh karena itu pelarangan SEMA nomor 3 tahun 2018 harus dibaca ulang serta dikaji lebih dalam demi kepentingan perempuan yang dipoligami siri.